Public-private partnerships, capital infrastructure project investments and infrastructure finance : public policy for the 21st century - Beckett-Camarata, Jane (Emerald Publishing Limited, 2020)
With the introduction of new market-oriented approaches to infrastructure finance policy decision-making in the national and subnational public sectors, there is a greater emphasis on the need for resource efficiency in the delivery of public services. There is also a critical need to evaluate and assess the effectiveness of infrastructure finance policy implementation. Public-Private Partnerships (PPPs) bring an agility and fresh perspective to the financing and delivery of public goods and services, and allow for a higher level of creativity, innovation, and flexibility during times of dynamic change and high demand for responsive solutions. By introducing a comprehensive new lens through which to view infrastructure finance policy as an instrument capable of achieving long-term national and subnational policy objectives, this study offers a unique insight into the potential benefits of the adoption of PPPs within the context of long-term capital investment planning. Through the examination of case studies from the United States, Albania and Mauritius, the author presents a transparent and integrated analysis of the role of PPPs as a policy option within this context. By demonstrating how PPPs can be utilized as a means of efficiently financing and delivering capital infrastructure projects within unified and comprehensive capital management and budgeting systems, this book is essential reading for researchers, policy decision-makers and students of public policy, capital budgeting and infrastructure finance.